Factors affecting fabric slipperiness. Issue 1 (January 2020) - Suganuma, Keiko; Itagaki, Masako; Kawada, Emi; Sasaki, Yumiko; Takemoto, Maki
Fabric slipperiness is an important property whose impacts include clothing comfort, sports records and the medical or safety performance of anti-slip or slippery textile products. The characteristics of fabric slipperiness have been studied under limited conditions and with samples with regard to the fabric component. In this study, the MIU (average value of the friction coefficient), which is correlated with the slipperiness or non-slipperiness of fabrics, and MMD (fluctuations of the average frictional coefficient), which is correlated with the smoothness or roughness, were measured for more than 50 versatile fabrics by using the friction tester, KES-SE. As a result, it was found that the friction coefficient was mainly determined by the linearity of weave texture, the fuzziness of the fabric and the real contact area between fabrics and rubbed materials, which are proposed as new factors of fabric slipperiness; this approach contrasts with the past approach, which mainly relied on the fabric structure. The relation between MIU and each factor was not analyzed separately but instead analyzed from a new comprehensive and statistical point of view. This approach made it possible to obtain the practical contribution ratio of these factors for application in the design of new slippery or anti-slip textiles that are useful for our lives. On the other hand, the smoothness had nothing to do with those factors, rather, it was related to the three-foundation weave texture of the fabrics.